Development and validation of an educational booklet for postpartum health and well-being - Eryjosy Marculino Guerreiro Barbosa; Sibele Lima da Costa Dantas; Dafne Paiva Rodrigues; Thereza Maria Magalhães Moreira; Maria Veraci Oliveira Queiroz; Mônica Oliveira Batista Oriá (Universidade Federal do Ceará, 2020)
Objective: to develop and validate the content and appearance of an educational booklet for the self-care of puerperal women. Methods: methodological research, consisting of five phases. In Phase 1, an integrative review and focus group were carried out to select the content. In Phase 2, the illustrations were created. Phase 3 was the development of the first version of the material. In Phase 4, the content was validated by 26 specialists. In Phase 5, fifteen puerperal women validated the appearance of the second version of the booklet. Results: content and appearance validities obtained validity indexes of 0.80 and 0.96, respectively; and agreement percentage of 94.75% and 100.0%, respectively. Conclusion: adequate indexes of validation of the educational booklet for health and well-being in the postpartum period were obtained.